Mapeamentos geoambientais, em escala 1:50.000, aplicados em análises de planejamento territorial de manancial periurbano : bacia do Ribeirão do Feijão, São Carlos, SP - Costa, Carlos Wilmer (Universidade Federal de São Carlos, 2017)
The fact that Ribeirão do Feijão basin (243.16km²) is a source of water supply for the city of São Carlos, the disorderly and, many times, chaotic urban sprawl, and the occurrence in its majority of the Botucatu Formation, were the reasons for this work. This way, studies involving physical medium (rocks, climate, relief, soil and water bodies), biotic (vegetation) and anthropic (soil cover and land use) attributes were developed. In this context, geoenvironmental mapping was a subsidy for the land planning with the elaboration of cartographic documents in a scale of 1:50.000, representing the basin environmental diagnosis. The main cartographic documents, elaborated from the matching of attributes in a GIS environment, were the charts of potential contamination of aquifers, surface runoff and accelerated erosion, and the basin geomorphologic map. The results evidenced that the analysis performed are compatible with the local conditions represented by the morphostructure of the Paraná Sedimentary Basin. The potential contamination of the aquifers varies from Medium to Very High due to the combination of land uses, resulting from the indiscriminate use of agrochemicals, overlay lithology and types of soils with sandy matrix, in low declivity terrains, thus favoring the infiltration of contaminants. In greater parts of the spring a low potential of surface runoff and Medium potential of accelerated erosion (86.12% of the basin) were also noted. In this case, the accelerated erosive process (381 ravines and 19 gullies) are directly related to sandy soil areas, extensive livestock and sugar-cane. The morphogenetic Neo-quaternary processes are intensified in areas of higher surface runoff, in the Sandy-Clay Hills of High Convex Hilltops, once they concentrate 32.8% of ravines and 21.1% of gullies. The recharge of groundwater is intensified in the Sandy Hills and in Low Convex Hilltops, once they are positioned in regions of low surface runoff potential, due to low declivities (between 0 and 10%), lithology and sandy soils.
Geoenvironmental mapping, 1:50,000 scale, applied in a territorial planning analysis of peri-urban water spring: Ribeirão do Feijão Basin, São Carlos, SP
Keywords: Geografia Física; Cartografia temática; Atributos Geoambientais; Geomorfologia; Antropoceno; CIENCIAS HUMANAS::GEOGRAFIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::GEOMORFOLOGIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::GEOLOGIA AMBIENTAL